Utility-scale wind power generation potential in low-wind regions: Insights for achieving the sustainable energy transition in developing countries - Tanoto, Yusak; Diprasetya, Leonardo; Enano, Nelson Jr; Warpindyasmoro, Heri Saptono (International Journal of Renewable Energy Development, 2026)
Wind energy represents a promising resource for accelerating the transition to renewable energy and meeting global net-zero emission targets. While wind turbines have generated considerable amounts of electricity in specific regions of four-season countries, their potential in low-wind countries is generally limited, thereby inhibiting further investigation. However, advancements in wind turbine design and wind resource databases have provided new opportunities for assessing utility-scale wind energy potential. Therefore, this study assessed the potential for utility-scale wind power generation in low-wind regions of Indonesia's Java–Bali region. The Weibull distribution of wind speed and theoretical energy output were investigated using 10-year hourly temporal-based wind speed data collected at 100 m height from 2006 to 2015. The National Renewable Energy Laboratory (NREL) power density classification was used to identify locations for energy generation analysis under wind turbine capacities of 1, 2, and 2.5 MW. The trade-offs between the average energy output over ten years and capacity factors were also considered. The results showed that the Ujungjaya area in Pandeglang Regency, Banten Province, has the potential to produce an estimated 13,916 MWh of energy per year using the 2.5 MW turbine with a capacity factor of 60.5% and Weibull parameters k and c of 2.49 and 8.22, respectively. The annual wind-based electricity generation potential of selected locations revealed that low-wind regions of Indonesia should not be overlooked when strategically planning wind energy utilisation to support the sustainable energy transition. In addition, the results have important implications for including additional wind energy in the energy mix of developing countries with similar low-wind regimes.